Nighttime secondary ozone layer during major stratospheric sudden warmings in specified‐dynamics WACCM. Issue 15 (9th August 2013) - Tweedy, Olga V.; Limpasuvan, Varavut; Orsolini, Yvan J.; Smith, Anne K.; Garcia, Rolando R.; Kinnison, Doug; Randall, Cora E.; Kvissel, Ole‐Kristian; Stordal, Frode; Harvey, V. Lynn; Chandran, Amal
Abstract : [1] A major stratospheric sudden warming (SSW) strongly impacts the entire middle atmosphere up to the thermosphere. Currently, the role of atmospheric dynamics on polar ozone in the mesosphere‐lower thermosphere (MLT) during SSWs is not well understood. Here we investigate the SSW‐induced changes in the nighttime "secondary" (90–105 km) ozone maximum by examining the dynamics and distribution of key species (like H and O) important to ozone. We use output from the National Center for Atmospheric Research Whole Atmosphere Community Climate Model with "Specified Dynamics" (SD‐WACCM), in which the simulation is constrained by meteorological reanalyses below 1 hPa. Composites are made based on six major SSW events with elevated stratopause episodes. Individual SSW cases of temperature and MLT nighttime ozone from the model are compared against the Sounding of the Atmosphere using Broadband Emission Radiometry observations aboard the NASA's Thermosphere Ionosphere Mesosphere Energetics and Dynamics (TIMED) satellite. The evolution of ozone and major chemical trace species is associated with the anomalous vertical residual motion during SSWs and consistent with photochemical equilibrium governing the MLT nighttime ozone. Just after SSW onset, enhanced upwelling adiabatically cools the polar region from 80 to 100 km and transports low H from below. These conditions promote a concentration increase in the secondary ozone layer. Subsequent downwelling from the lower thermosphere warms the MLT and enhances the descent of H from the thermospheric reservoir, thereby limiting the secondary ozone concentration increase. Negative correlation of secondary ozone with respect to temperature and H is more pronounced during winters with SSWs than during non‐SSW winters. Key Points: MLT ozone changes during SSW are associated with anomalous residual motion. MLT ozone changes during SSW are consistent with photochemical equilibrium. Specified Dynamics WACCM captures realistic SSW.